Soil health assessment: Past accomplishments, current activities, and future opportunities - Karlen, Douglas L.; Veum, Kristen S.; Sudduth, Kenneth A; Obrycki, John F.; Nunes, Márcio R. (Soil & tillage research, 2019)
•Evolution of the soil health concept is presented.•Increased private sector support has significantly accelerated awareness of and interest in soil health.•Soil biological properties and processes are the new frontiers in soil health.•Sensor development for in-situ assessment is advancing the science of soil health assessment. Global interest in soil health has increased exponentially during the past decade, with many different government, non-government, and private sector groups striving to develop monitoring and assessment protocols. This brief review focuses on developments in the United States (U.S.) with some references to activities in other countries. It also documents how the soil health concept evolved and projects what is needed to scientifically advance monitoring and assessment with a particular focus on activities in the U.S. Recommendations emphasize improving the Soil Management Assessment Framework (SMAF) and/or Comprehensive Assessment of Soil Health (CASH) assessment tools, developing protocols for national soil health monitoring, identifying and calibrating better indicators of soil biological, chemical, and physical health, and developing sensors and other tools for more rapid and in-situ assessments. Collectively, these and other research and technology transfer activities will help achieve what we suggest should be a universal goal – striving for healthy soils, healthy landscapes, and vibrant economies.